Traumatized Bodies/Minds in Angela Carter’s Works: A Study of Disabled Characters’ social exclusion towards a more inclusion - Krifa, Wiem (Eddissi Languages Journal, 2026)
Angela Carter’s works exhibit social exclusion of people with disabilities. Referring to the social and medical models of disability studies, the writer highlights the role society plays in enhancing disabled persons’ predicaments. In Nights at The Circus, Fevvers’ and Toussaint’s social exclusion hinders their progress and limits their economic independence. Society proves to be responsible for their marginalization and undermined position. What the writer advances in her narrative is a more social inclusive framework that backs disabled people and ushers them into equality and justice. The way the writer studies disability in relation to gender opens further horizons for the female disabled category. In her short story “The Bloody Chamber”, the writer deconstructs the internalized social prejudices based on unjust beauty and normalcy criteria. The blind music tuner’s moral beauty provides him with a deep insight that empowers him over the abled Marquis.